Les désastres de la guerre - Jean-Philippe Chimot (Amnis)
Realized between 1810 and 1820, then published in 1863, Goya’s etchings entitled Disasters of War imposed on the art world a new way of viewing war, perceived as a brutal clash between torturers and their victims. For this conflict with no holds barred, Goya invents an iconography less noble than the contemporary styles (late Rococo or Neo-Classical), without however falling victim to the inevitable opportunism of the period’s popular engravings. Today, the strength of Goya’s Disasters lies perhaps in his premonition of the unbearable cruelty that nations reserve for one another, as though the Enlightenment had from that moment on accentuated the shadows which are still surrounding us.